2015
DOI: 10.1002/masy.201400111
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Properties of Acrylonitrile‐Butadiene‐Styrene/ZnO Nanocomposites with Compatibilizer

Abstract: Summary: This work investigated the effects of polystyrene-co-maleic anhydride (SMA) compatibilizer on morphology and properties of acrylonitrile-butadienestyrene (ABS)/zinc oxide (ZnO) nanocomposites. The ABS/ZnO nanocomposites were prepared by using an internal mixer and were then molded by compression method. In order to improve adhesion between the filler and the matrix, SMA has been used as compatibilizer in the nanocomposites. ABS/ZnO nanocomposites showed the storage modulus increased with increasing Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Four studies were identified that complied with the criteria: two studies of PLA [13,24] and two of ABS [19,37]. Utilising the recalculation method detailed above, the revised strength increased in all studies and fell within the range for bulk materials indicated in the literature [11,12,[38][39][40][41]13,[29][30][31][32][33][34][35] (Fig. 17 (a) -(d)).…”
Section: Ashby Plotsmentioning
confidence: 92%
“…Four studies were identified that complied with the criteria: two studies of PLA [13,24] and two of ABS [19,37]. Utilising the recalculation method detailed above, the revised strength increased in all studies and fell within the range for bulk materials indicated in the literature [11,12,[38][39][40][41]13,[29][30][31][32][33][34][35] (Fig. 17 (a) -(d)).…”
Section: Ashby Plotsmentioning
confidence: 92%
“…SEBS- g -MA was chosen to be used as a reactive compatibilizer to improve the interfacial adhesion between the ABS matrix and the FR additives, which contain mostly hydrophilic end groups. SEBS- g -MA has been used in styrenic polymers to improve their compatibility with nature-derived additives, including TA, FG, and ME, , and similar compatibilizers, also based on styrene and maleic anhydride, have been used in ABS composites. ,, …”
Section: Resultsmentioning
confidence: 99%
“…SEBS-g-MA has been used in styrenic polymers to improve their compatibility with nature-derived additives, including TA, FG, and ME, 28,63 and similar compatibilizers, also based on styrene and maleic anhydride, have been used in ABS composites. 48,51,64 Irganox 1010 (Irg), a strong antioxidant, has been shown to be important in protecting tannic acid from thermo-oxidative degradation during processing in polyolefins. 28 Irg was therefore selected to be used in every tannic acid-containing sample in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Copolymers based on MA and styrene can be especially effective in styrenic polymers, such as ABS [28]. SEBS-g-MA has been used in styrenic polymers (PS and HIPS) to improve their compatibility with nature-derived additives, including TA, FG and ME [18,101]; other styrene-and MA-based copolymers have been used as compatibilizers in ABS composites, including those filled with a bio-based FR agent, lignin [26,33,102].…”
Section: Onementioning
confidence: 99%
“…Maleated coupling agents are often chosen for this function, as the hydrophobic portion of the compound can blend well with the polymeric matrix while the maleic anhydride (MA) groups can react with the fillers' hydrophilic end groups. Styrenic compounds grafted or copolymerized with MA are good candidates to be used in ABS due to the presence of styrene in the terpolymer; styrene-and MA-based compatibilizers have been used frequently in ABS composites [18,26,33,101,102].…”
Section: Selection Of Type and Amount Of Compatibilizermentioning
confidence: 99%